Dataset of NIR, MIR and FIR spectroscopy of fuels in maritime cases and biodiesel-diesel blends B7 and B10 from Malaysia - Abdull Manap, Mohd Rashidi; Baharim, Haziq Izwan; Shamsudin, Nur Azalina Ajmahera; Ferdaus, Ahmad Faridi (Elsevier BV, 2024)
The dataset contains Fourier-transform infrared (FTIR) spectroscopic analysis of fuels in maritime cases and biodiesel–diesel blends B7 and B10 from Malaysia. Fuels in maritime cases were donated by Agensi Penguatkuasaan Maritim Malaysia (APMM) in March 2023. The crime-related oil samples originated from maritime crime scenes located within Terengganu and Johor, Malaysia. Meanwhile, B7(DE5) and B10(D0) samples were obtained from pump stations in 2021. They are fuels used in Malaysian transportation system. The FTIR analysis was acquired in the full regions of FTIR (6000–80 cm−1) which are near-infrared (NIR), mid-infrared (MIR), and far-infrared (FIR). The IR spectra were recorded using Bruker Invenio-R (Universiti Putra Malaysia) spectrometer equipped with attenuated total reflection (ATR) (2 mm) diamond with an accumulation of 64 scans at a spectral resolution of 4 cm−1. Spectral analysis was carried out by OPUS 8.7.41. The data highlights the potential of NIR, MIR, and FIR spectroscopy as a powerful tool for forensic analysis in maritime crime investigations. This includes the potential of utilizing the Hierarchical Clustering Analysis (HCA) to discriminate between type of fuels in forensic cases